(3YHK GdhdjO aj GdcdGe Ydi TYQ CHj oYHGOI GdhdjOs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s; (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s ((3GdeOQSI GdeMehOjI HGdeOjfI GdefhQI s)
(3ChdgG (B:s
(3KHJ aj OjhGf GdHMJQj eeG CUdM ef GdZdW s
(3BNQgG (B:s
(3jLH Cf JKHJ aj MQa GdgGA CjVkG, Je GdEedGA GdeYQha HYHK GdhdjO hHGddg GdJhajb s
(3HgG fXGe GdJYbjHIs
(3JJab eY GdfSNI GdChdi aj ChdgG hBNQgG HGNJdGa aj HYV GdCdaGXs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs